2020
DOI: 10.1101/2020.02.17.20024257
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tracking and Predicting COVID-19 Epidemic in China Mainland

Abstract: By proposing a varying coefficient Susceptible-Infected-Removal model (vSIR), we track the epidemic of COVID-19 in 30 provinces in China and 15 cities in Hubei province, the epicenter of the outbreak. It is found that the spread of COVID-19 has been significantly slowing down within the two weeks from January 27 to February 10th with 87.0% and 84.3% reductions in the reproduction number R0 among the 30 provinces and 15 Hubei cities, respectively. This suggests the extreme control measures implemented since Jan… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
57
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 14 publications
0
57
1
2
Order By: Relevance
“…Let the unit time be 1 day. Based on the previous studies [6,7], we fix 1/ε = 5, and thus, ε = 0.2 and γ = 0.1, respectively. We fix S + E + I + R to be 1 so that each population implies the proportion to the total population.…”
Section: Modelmentioning
confidence: 99%
“…Let the unit time be 1 day. Based on the previous studies [6,7], we fix 1/ε = 5, and thus, ε = 0.2 and γ = 0.1, respectively. We fix S + E + I + R to be 1 so that each population implies the proportion to the total population.…”
Section: Modelmentioning
confidence: 99%
“…A temporary reduction in σ can account for both population-wide interventions and interventions specific to identified infectious (or possibly infectious) individuals. The SIR model with a time-dependent reproduction number (or equivalently, a time-dependent contact rate) has been considered before, for instance in [3,22]. Typically, an epidemic does not result in substantial permanent change in the contact rate of a population.…”
Section: Problem Description and Assumptionsmentioning
confidence: 99%
“…According to (22), the optimal control value will switch when u x = u y , which leads to (19). Meanwhile, substituting (22) in (21) in the case u y < u x yields the linear hyperbolic PDE u t = γyu y − βxy(u y − u x ), whose characteristics are just the trajectories of the SIR system (1) illustrated in Figure 1, which are also contours of x ∞ . It can be shown that once u y − u x < 0, this inequality will continue to hold along each such characteristic.…”
Section: Infinite-time Controlmentioning
confidence: 99%
“…Many researchers have conducted mathematical model-based studies to investigate the transmission dynamics and forecast the number of COVID-19 infections. A mathematical susceptible-infectious-recovered (SIR) and susceptible-exposed-infectious-recovered (SEIR) were considered to forecast the number of coronavirus infections in China [7,8]. A flowchart of the SIHR model is presented in Figure 3 Based on the mathematical model described above, the time-varying transmission rate is considered as follows:…”
Section: Statistical Modelmentioning
confidence: 99%